बुद्ध-धम्म के उत्थान में बिहार की महान् भिक्खुनियों एवं उपासिकाओं का योगदान: The Contribution of Eminent Bhikkhunis and Upasikas of Bihar in the Rise of Buddhism (Bodhi Path, 2025)
This research paper delves into the influential role played by the women of Bihar—specifically bhikkhunis (ordained nuns) and upasikas (lay female followers)—in the development and propagation of Buddhism during and after the time of the Buddha. It provides a socio-historical analysis of how these women overcame deep-rooted patriarchal norms to become pivotal figures in religious reform and spiritual leadership.The study foregrounds the active involvement of notable female figures such as Mahapajapati Gotami, Khema, Patacara, Dhammadinna, Bhadda Kundalakesa, and Visakha, among others. Drawing on canonical sources like the Therigatha and Jataka Tales, the paper chronicles their personal transformations—from royal consorts, aristocrats, and courtesans to enlightened bhikkhunis—revealing how each woman’s spiritual journey became a testimony to inner resilience and dharmic conviction.Through these biographies, the paper highlights themes of gender equality, renunciation, spiritual discipline, and the struggle against societal injustices. It also underscores Bihar’s historical significance as a cradle of early Buddhist education, monastic culture, and women's emancipation within the Buddhist sangha.A significant part of the study is devoted to Sanghamitta's mission to Sri Lanka, where she established a bhikkhuni sangha, emphasizing the transnational impact of Bihar’s Buddhist women. The author argues that this legacy of inclusion and spiritual contribution laid the foundation for a more egalitarian vision of society.
Keywords: Mahapajapati Gotami; Khema; Patacara; Dhammadinna; Bhadda Kundalakesa; Visakha; भिक्खुनियों एवं उपासिकाओं का योगदान; बुद्ध-धम्म के उत्थान में बिहार